2018
DOI: 10.1080/02619768.2018.1448783
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to analyse pupils’ learning within coursework on campus: a remaining challenge in teacher education

Abstract: To support pupils' learning, teachers must understand what and how their pupils have learned, and teacher education should teach candidates how to do this. This article reports on survey data (n = 270) from three programmes and observation data (N = 104 hours) from six programmes, located in Norway, Finland and the US. It examines the candidates' opportunities to analyse pupils' learning within their coursework. The authors argue that such opportunities might constitute profound possibilities to examine the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…Experiencing few opportunities to examine own pupils' work might be explained by the fact that only students in the Stanford and Varona programme had concurrent field placement and a responsibility for their 'own' pupils. The candidates' perception of few opportunities to examine transcripts aligns with the findings by Jenset, Canrinus et al (2018), who observed that candidates were offered few opportunities to analyse pupils' learning.…”
Section: Prioritizing Opportunities To Enact Practicesupporting
confidence: 80%
See 3 more Smart Citations
“…Experiencing few opportunities to examine own pupils' work might be explained by the fact that only students in the Stanford and Varona programme had concurrent field placement and a responsibility for their 'own' pupils. The candidates' perception of few opportunities to examine transcripts aligns with the findings by Jenset, Canrinus et al (2018), who observed that candidates were offered few opportunities to analyse pupils' learning.…”
Section: Prioritizing Opportunities To Enact Practicesupporting
confidence: 80%
“…They also contended that in campus courses, relatively little time was used to analyse pupils' work or other artefacts used in classrooms. A recent study presenting findings from observations of methods courses in a Finnish, a Norwegian and an American teacher education programme (Jenset, Canrinus et al, 2018) supports these statements. Hammerness (2013) underlines that many Norwegian teacher educators and programme directors draw a clear distinction between the mainly theoretical university courses and the practical work taking place at the schools.…”
Section: The Enactment Of Practicementioning
confidence: 88%
See 2 more Smart Citations
“…An alternative perspective on quality in teacher education focuses on closer links between preparation and practice through field experiences and school placements (see . Such experiences offer teachers an opportunity to rehearse teaching and observe studentsí learning (Jenset, Canrinus, Klette, & Hammerness, 2018). Other perspectives focus on the quality of teaching in terms of linking theory with practice and having shared visions of what constitutes good teaching to inform curriculum and pedagogy (Hammerness & Klette, 2015).…”
Section: Qualitymentioning
confidence: 99%